Are muscle forces relevant in the age related rise of injuries in adolescent soccer players? - Durpre, T.; Mortensen, K. R. L.; Gertz Lysdal, F.; Funken, J.; Muller, R.; Mayer, J.; Krahl, H.; Potthast, W. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was the comparison of the kinematics and kinetics in soccer inside passes between three age groups (U12, U16, U23). Using 3D movement analysis and inverse dynamics, hip joint kinematics and adductor muscle forces were calculated. SPM analysis showed significant differences in adduction angle and velocity and in muscle forces of adductor longus and gracilis. Comparison of the muscle forces shows a rapid increase in muscle forces from the youngest children to the adolescents while the difference between the adolescents and adults is only minor. It seems reasonable, that the fast development of muscle forces in adolescents compared to the slower development of the tendons is a factor in the sudden rise in injury incidence at the beginning of puberty. Therefore, adolescent players should be trained with caution to avoid early injuries.